2019
DOI: 10.1080/13607863.2019.1617239
|View full text |Cite
|
Sign up to set email alerts
|

Art activities and qigong exercise for the well-being of older adults in nursing homes in Indonesia: a randomized controlled trial

Abstract: Objective: This study aims to investigate the effect of an integrated intervention of art activities and Qigong exercise on the well-being of older adults in nursing homes in Indonesia. Method: We employed a randomized controlled trial with 4 specific groups, i.e. art, Qigong, integration of art and Qigong, and control group. A total of 267 participants aged 50 years or older were recruited from 9 nursing homes in Jakarta, Indonesia. The participants were randomly allocated to one of the four groups, attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Although the variation between the included studies with regard to experimental design (i.e., RCT vs. NRS) may produce inherent bias of the pooled data, the results suggest that Qigong has the potential to relieve psychological stress by regulating cortisol level. Previous studies mainly focused on identifying dose-response effect of exercise and physical activity for self-perceived psychological outcomes (Tsang et al, 2008 ; Wang et al, 2009 ; Roswiyani et al, 2019 ). Similarly, the included studies rarely used objective measures of psychological outcomes, restricting the possibility to conduct further meta-analysis on these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although the variation between the included studies with regard to experimental design (i.e., RCT vs. NRS) may produce inherent bias of the pooled data, the results suggest that Qigong has the potential to relieve psychological stress by regulating cortisol level. Previous studies mainly focused on identifying dose-response effect of exercise and physical activity for self-perceived psychological outcomes (Tsang et al, 2008 ; Wang et al, 2009 ; Roswiyani et al, 2019 ). Similarly, the included studies rarely used objective measures of psychological outcomes, restricting the possibility to conduct further meta-analysis on these variables.…”
Section: Discussionmentioning
confidence: 99%
“…14 In Indonesia, the prevalence of depression among nursing home population is quite high (42.5%), and this has been attested by the evidence of high demand for nursing home programs that are suitable for accommodating the elderly’s physical and mental health. 15 A study conducted by Hanum et al 16 showed a high prevalence of psychological issues among the elderly, where 32.72% of the study sample experienced depression. According to Wahyuningsih et al, 17 the risk of depression rose with the experience of chronic illness, social isolation, and loneliness.…”
Section: Introductionmentioning
confidence: 90%
“…Regarding treatment duration, although data were missing in some studies, interventions lasted mostly for 4-8 weeks. With more detail, 13 studies (21,22,27,39,44,45,52,54,55,63,68,71,77) described 8 weeks interventions. Exceptions were the Llewellyn-Jones et al (26) and the Leontjevas et al (66) studies, which included an assessment after 9.5 and 20 months, respectively.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Exceptions were the Llewellyn-Jones et al (26) and the Leontjevas et al (66) studies, which included an assessment after 9.5 and 20 months, respectively. Usually, treatment sessions had a weekly frequency, higher in some studies (2/week) (38,39,44), (3/week) (61,65) and lasted 30 to 60 min (21,27,41,45,47,48,53,57,59,77).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation